(untitled) (BIS Humanities and Social Science, 2026)
The study examines recurring ecological disasters in Sumatra, including deforestation, peatland degradation, and agrarian conflicts, as symptoms of constitutional failure rather than isolated environmental or administrative lapses. Employing a socio-legal approach based on empirical evidence from Aceh, North Sumatra, and West Sumatra, the research analyzes the gap between Indonesia’s constitutional mandates for environmental protection (Articles 28H(1) and 33(4) of the 1945 Constitution) and their implementation. The novelty of this study lies in its reinterpretation of ecological disasters as constitutional warnings and manifestations of intergenerational injustice, a perspective largely overlooked in existing discourse on Green Constitutionalism in Indonesia. The main findings reveal that although constitutional provisions are symbolically acknowledged, their interpretation remains anthropocentric and short-term oriented, thereby transferring ecological risks to future generations without adequate legal safeguards. The article concludes that a paradigmatic shift toward a substantive constitutional approach, embedding principles of precaution, non-regression, and state trusteeship, is essential to prevent the constitution from failing in its role as a guardian of long-term public and ecological interests.